Induction of Cross-Clade Antibody and T-Cell Responses by a Modified Vaccinia Virus Ankara–Based Influenza A(H5N1) Vaccine in a Randomized Phase 1/2a Clinical Trial. (18th April 2018) - de Vries, Rory D; Altenburg, Arwen F; Nieuwkoop, Nella J; de Bruin, Erwin; van Trierum, Stella E; Pronk, Mark R; Lamers, Mart M; Richard, Mathilde; Nieuwenhuijse, David F; Koopmans, Marion P G; Kreijtz, Joost H C M; Fouchier, Ron A M; et al.
Abstract : The modified vaccinia virus Ankara (MVA) H5 influenza vaccine induced immune responses that display remarkable cross-reactivity with a variety of H5 viruses. We hypothesize that this MVA-H5 vaccine could provide immunity to protect against a large variety of antigenically distinct influenza viruses of the H5 subtype. Abstract: Background: High-pathogenicity avian influenza viruses continue to circulate in poultry and wild birds and occasionally infect humans, sometimes with fatal outcomes. Development of vaccines is a priority to prepare for potential pandemics but is complicated by antigenic variation of the surface glycoprotein hemagglutinin. We report the immunological profile induced by human immunization with modified vaccinia virus Ankara (MVA) expressing the hemagglutinin gene of influenza A(H5N1) virus A/Vietnam/1194/04 (rMVA-H5). Methods: In a double-blinded phase 1/2a clinical trial, 79 individuals received 1 or 2 injections of rMVA-H5 or vector control. Twenty-seven study subjects received a booster immunization after 1 year. The breadth, magnitude, and properties of vaccine-induced antibody and T-cell responses were characterized. Results: rMVA-H5 induced broadly reactive antibody responses, demonstrated by protein microarray, hemagglutination inhibition, virus neutralization, and antibody-dependent cellular cytotoxicity assays. Antibodies cross-reacted with antigenically distinct H5 viruses, including the recently emerged subtypes H5N6 and H5N8 and the currently circulating subtype H5N1. In addition, the induction of T cells specific for H5 viruses of 2 different clades was demonstrated. Conclusions: rMVA-H5 induced immune responses that cross-reacted with H5 viruses of various clades. These findings validate rMVA-H5 as vaccine candidate against antigenically distinct H5 viruses. Clinical Trials Registration: NTR3401.